Mean GOSLON Yardstick Scores After 3 Different Treatment Protocols—A Long-term Study of Patients With Unilateral Cleft Lip and Palate. (February 2019) - Peterson, Petra; Mars, Michael; Gowans, Alan; Larson, Ola; Neovius, Erik; Henningsson, Gunilla; Andlin-Sobocki, Anna; Pegelow, Marie; Lemberger, Mathias; Raud-Westberg, Liisi M.; Karsten, Agneta L-A
Objectives: (1) To evaluate dental arch relationships, with the Great Ormond Street, London and Oslo (GOSLON) Yardstick, of participants with Unilateral cleft lip and palate (UCLP) and treated with 1-stage palatal closure with 3 different surgical protocols (2) to compare the mean GOSLON ratings with other CLP centers. Design: Retrospective study of medical charts and dental models. Setting: Karolinska University Hospital, Stockholm, Sweden. Participants: Eighty-seven patients with UCLP operated with 1-stage palatal repair. Thirty-five were operated with Veau-Wardill-Kilner (VWK) technique 1975 to 1986, 31 with minimal incision technique (MIT) from 1987 to 1997, and 21 according to MIT with muscle reconstruction (MITmr) 1998 to 2004. Interventions: Dental casts at ages 5 (n = 87), 7 to 8 (n = 27), 10 (n = 81), 16 (n = 61), and 19 (n = 35) years were rated by 10 assessors with the GOSLON Yardstick. Information of other interventions was retrieved from patients' charts. Main outcome measures: Mean GOSLON ratings. Results: A total of 82% of the participants were rated as having excellent to satisfactory outcome. Weighted κ statistics for the 10 assessors was good for inter-rater agreement and good/very good for intra-rater agreement. Conclusions: The mean GOSLON score in the Stockholm overall material at age 10 was 2.67. The VWK technique resulted in a greater need of orthognathic surgery than the MIT ( P < .01). The MITmr did not produce better dental arch relationships than MIT at age 5 ( P < .05). The best dental arch relationships were found in the MIT group at 10 years, mean 2.58, which is not significantly different from other centers with excellent outcome except Gothenburg and Vienna.